Endoscopic treatment of biliary complications after pediatric liver transplantation in a high volume transplant center in Turkey - Harputluoglu, M. M. M.; Aladag, M.; Bilgic, Y.; Erdogan, M. A.; Caliskan, A. R.; Selimoglu, A.; Yilmaz, S. (Lippincott Williams & Wilkins, 2018)
[Abstract Not Available]
Joint International Congress of ILTS, ELITA and LICAGE -- MAY 23-26, 2018 -- Lisbon, PORTUGAL
Keywords: Pediatric; liver transplantation; biliary complication; endoscopic retrograde cholangiopancreatography